Mini review: recent advances in biosurfactant-based association colloids–formation of microemulsions - Hellweg, Thomas; Oberdisse, Julian; Sottmann, Thomas (Frontiers in Soft Matter, 2023)
In the context of a more sustainable economy, bio-surfactants become increasingly important, due to their independence of petrol-based chemistry, their usually mild synthesis conditions, and in certain cases their pharmacological activity. We have recently discussed self-assembly studies in binary systems of bio-surfactants of microbial origin, or saponins extracted from plants (Hellweg et al. 2023). In the present review, we focus on the formation of microemulsions based on these molecules. We review the formation and structure of microemulsion systems formed by oil, water, and biosurfactants, with a particular focus on Quillaja saponins and rhamnolipids.